Role of Tetraspanins in Hepatocellular Carcinoma - Cai, Sicheng; Deng, Yue; Peng, Huiming; Shen, Jian (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is characterized by high prevalence, morbidity and mortality. Liver cancer is the sixth most common cancer worldwide, and its subtype, HCC, accounts for nearly 80% cases. HCC progresses rapidly, and for now there is no perfect treatment for advanced HCC. Tetraspanins belongs to a protein family featured by four transmembrane domains. 33 tetraspanins are widely expressed on the surface of most nucleated cells and play important roles in different biological processes. In our review, we summarize the functions of tetraspanins and underlying mechanism in the whole life cycle of HCC, from its initiation, progression and finally to treatment. Generally, CD9, TSPAN15, and TSPAN31 can promote HCC cells proliferation or suppressing apoptosis. CD63, CD151, and TSPAN8 can facilitate HCC metastasis somehow, while CD82 serves as a suppressor of metastasis. TSPAN1, TSPAN8 and CD151 act as prognosis indicator, proven to be inversely correlated to the overall survival rate of HCC patients. Beyond this, we also discuss the potential of tetraspanin family as novel therapeutic target and solution to drug resistance, and provide some suggestions for further research.